Purisme på hell? Nye tendensar i nynorsk ordforrådsnormering - Vikør, Lars S. (Nordiske Studier i Leksikografi, 2001)
One of Norway’s two written Janguages, Nynorsk, is marked by a selective purism: it accepts internationalisms readily, but rejects many loans from Danish and Low German. This policy has been modified over time, however, and it is controversial among the users of the language. The paper discusses the nature of Nynorsk purism, the main arguments for and against, and the recent developments in the Norwegian Language Council, which is the highest formal authority in the field of Norwegian language cultivation.